Health Education for Elementary School Age Children in the Kenosis Community, Surabaya - Juliana Christyaningsih; Yuni Ginarsih; Kasiati; Mujayanto; Nuning Marina Pengge; Kiaonarni O.W; Pratiwi Hermiyanti; Rahayu Sumaningsih; Lembunai Tat Alberta; Evi Yunita Nugrahini; Yohanes Kambaru W; Teta puji Rahayu; Nurwening TW; Hery Sumasto; Suliati; Lully Hani Endarini; Evy Diah Woelansari; Ira Puspita Sari; Ira Rahayu Tiyar; P, Teresia Retna; Museyaroh (Frontiers in Community Service and Empowerment, 2026)
ABSTRACT The tutoring center "Kenosis" in Sidoyoso, established in 2016 by GKA Gloria Pos Sidoyoso, provides free educational support for elementary school children. This program helps in the academic and character development of children, initially taught by instructors from the Inter-University Christian Fellowship (Perkantas) and now reinforced by 4 permanent teachers. In addition to the need for tutoring, children are faced with daily conditions such as unhealthy snacks, low understanding of dental hygiene, and the importance of handwashing. These bad habits increase the risk of dental caries, infectious diseases, and the consumption of harmful food additives. Education and supervision are key to improving children's health and well-being. The Poltekkes Kemenkes Surabaya service team, consisting of 21 lecturers and 11 students, provided solutions to the above issues to 35 elementary school children at the Kenosis tutoring center on January 9, 2025, by delivering educational materials and practicing how to choose healthy snacks, brush teeth, and wash hands properly and correctly. Knowledge of harmful food additives The average pre-test score was 60.2, while the post-test score was 70.5. Understanding of proper tooth brushing techniques pre-test result 60.0 and post-test 70.5, understanding of good and correct handwashing habits had an average pre-test score of 60.0 and a post-test score of 70.5. There was an increase in knowledge about harmful food additives, proper tooth brushing techniques, and proper handwashing at the "Kenosis GKA Gloria Pos Sidoyoso" tutoring session. INDEX TERMS GKA Gloria, preservatives, food, PHBS, teeth.